Postpartum anoestrus in the suckled swamp buffalo - Sharifuddin, W.; Jainudeen, Mohamed Razeen; Yap, Keng Chee; Dahari, A. Bakar (IAEA, 1984)
Postpartum anoestrus is a serious cause of infertility in the swamp buffalo. Our studies have revealed that it is due to a failure in the resumption of ovarian cyclicity. Parity was inversely related to the calving interval being longer in primiparous than multiparous suckled buffaloes. This effect may be partly due to the higher nutrient demands for growth as well as for lactation in the primiparous animal. The effects of suckling on ovarian and pituitary function of postpartum buffaloes were investigated with the aid of radioimmunoassays for progesterone and luteinizing hormone (LH) as well as rectal palpation and laparoscopic inspection of the ovaries. The incidence of postpartum anoestrus was higher in suckeld than non-suckled buffaloes. Weaning buffalo calves at 30 d post partum resulted in the resumption of normal ovarian cycles within 60 d post partum. LH release in response to a single injection of a synthetic gonadotropin releasing hormone (GnRH) indicated that pituitary responsiveness to GnRH was restored by Day 30 post partum in suckled buffaloes whereas anoestrous buffaloes were able to release levels of LH comparable to that of the preovulatory surge. A progesterone-releasing intra-vaginal device (PRID) induced an anovulatory oestrus in the anoestrous suckled buffalo which was partially overcome by human chorionic gonadotropin (HCG) administered at the induced oestrus. However, a 72 h separation of the calf from its dam combined with PRID was the most effective substitute to weaning in initiating ovarian cycles in the suckled buffalo. Our data suggest that suckling inhibits ovarian function not by an effect on the pituitary gland but rather on GnRH release by the hypothalamus.